Respuesta :

9514 1404 393

Answer:

  (x, y) = (10, 6)

Step-by-step explanation:

Any of the usual methods work to solve this: elimination, substitution, graphing, matrix methods. For a "no-work" solution, I prefer a graphing calculator.

__

In the second equation, both x and y have coefficients of ±1, so substitution or elimination can be used with equal ease. Adding x to the second equation gives an expression for y that can be substituted in the first equation.

  y = x -4

  -3x +8(x -4) = 18

  -3x +8x -32 = 18 . . . eliminate parentheses

  5x = 50 . . . . . . . . . add 32, collect terms

  x = 10 . . . . . . . . . . .divide by 5

  y = 10 -4 = 6 . . . . . use the expression for y to find y

The solution is (x, y) = (10, 6).

Ver imagen sqdancefan